China studies in South and Southeast Asia between pro-China and objectivism - Shi, Zhiyu 1958-; Manomaivibool, Prapin; Marwah, Reena 1960- (World Scientific Publishing Co. Pte. Ltd., 2019)
The rise of China has reconstituted the regional identity in Asia as well as the lens through which understanding of China and self-understanding are no longer separate processes intellectually. China scholarship in South and Southeast Asia necessarily highlights meanings of encountering China that Western social sciences fail to reflect because academics in many places, being migrants, navigate and combine more than one civilization forces. With China in itself undergoing transformation, it is unlikely that one can simply speak of China without multiple qualifications of what one actually refers to. The book gathers authors who come from different scholarly traditions to reflect upon how the presentation of China in academic writings as well as think tank analyses can engender different identity possibilities. The book therefore complicates the category "China" to enable mutual empathy between everything that in one way or another relies on Chineseness as object or subject in accordance with the identity strategies of the China experts